Growing electrostatic modes in the isothermal pair plasma of the pulsar magnetosphere - U. A., Mofiz; Amin, Md. Ruhul; Shukła, Padma Kant (© 2011 Springer Science+Business Media B.V., 2016)
This article was published in the Astrophysics and Space Science [© 2011 Springer Science+Business Media B.V.] and the definite version is available at : http://dx.doi.org/10.1007/s10509-011-0845-0. The Journal's website is at: http://link.springer.com/article/10.1007%2Fs10509-011-0845-0